Redes de imagens, memórias e testemunhos: por uma documentação performativa de saberes - Guggisberg, Sonia (2014)
The objective of this thesis is to analyze and expand the traditional format of documentary film, highlighting its political role from transmedia experiments carried out in the city of Sao Paulo. The main hypothesis is that, from the transit between fictional and real images, triggers off a performative documentation of knowledge. This hypothesis suggests an experimental methodology to document and reflect on different political and cultural contexts of the city. To get to this formulation, the thesis related Boaventura de Souza Santos concept of ecology of knowledges to Michel Foucault s concept of archives, Giorgio Agamben s concept of testimony as well as political performative proposed by Diana Taylor. To, specifically, analyze the changes in the concept of film documentary, the thesis departs from the definition of film essay, developed by Arlindo Machado, contextualizing it in relation to the discussions of image by Gilles Lipovetsky. Finally, the thesis discusses the relationship between document and translate, proposing four experiments that constitute the corpus of the thesis: The documentary Subsoil (about abandoned and buried underground spaces along Avenida Paulista); The video installation Urban Waterfalls that liquefies the structures of the city in a continuous movement of scenes whose violence is expressed in image and sound; Castle of Cards that builds a testimony on the dismantlement of the city in a mosaic of nine simultaneous screens; and the Eco Systems that draw up a proposal of collective sharing of artistic language and unpublished works designed by a group of guests. These experiences are the main result of the research